The somatic mutation landscape of premalignant colorectal adenoma. Issue 7 (12th June 2017) - Lin, Shu-Hong; Raju, Gottumukkala S; Huff, Chad; Ye, Yuanqing; Gu, Jian; Chen, Jiun-Sheng; Hildebrandt, Michelle A T; Liang, Han; Menter, David G; Morris, Jeffery; Hawk, Ernest; Stroehlein, John R; et al.
Abstract : Objective: There are few studies which characterised the molecular alterations in premalignant colorectal adenomas. Our major goal was to establish colorectal adenoma genome atlas and identify molecular markers of progression from colorectal adenoma to adenocarcinoma. Design: Whole-exome sequencing and targeted sequencing were carried out in 149 adenoma samples and paired blood from patients with conventional adenoma or sessile serrated adenoma to characterise the somatic mutation landscape for premalignant colorectal lesions. The identified somatic mutations were compared with those in colorectal cancer (CRC) samples from The Cancer Genome Atlas. A supervised random forest model was employed to identify gene panels differentiating adenoma from CRC. Results: Similar somatic mutation frequencies, but distinctive driver mutations, were observed in sessile serrated adenomas and conventional adenomas. The final model included 20 genes and was able to separate the somatic mutation profile of colorectal adenoma and adenocarcinoma with an area under the curve of 0.941. Conclusion: The findings of this project hold potential to better identify patients with adenoma who may be candidates for targeted surveillance programmes and preventive interventions to reduce the incidence of CRC.